2018
DOI: 10.22531/muglajsci.421813
|View full text |Cite
|
Sign up to set email alerts
|

Geri̇ Dönüştürülmüş Ve Doğal Malzeme Kullanilarak Üreti̇len Sandvi̇ç Kompozi̇tleri̇ni̇n Eği̇lme Davranişlari

Abstract: Recently, for making the low-cost engineering materials the use of natural fibers as reinforcement in polymers composites has brought forth a lot of interest. The use of natural products instead of synthetic materials reduces the amount of carbon released into the atmosphere. Nevertheless, reuse of used materials by recycled is important both for the environment and for economic reasons. In this study, flexural behaviors of sandwich composites manufactured by using natural and recycled material were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…They investigated the effects of some parameters such as filler content, jute fibers orientation, and core thickness on the bending, ballistic, and compression characteristics of the developed structure. Using waste materials and natural-based fibers, Balcioglu [142,143] analyzed the flexural, tensile, and compressive properties of sandwich structures consisting of vehicle tire rubber in the core and woven jute/epoxy composite in the face sheets. Rajole et al [144,145] analyzed the impact response of jute/epoxy/rubber sandwich panels and compared their performance with that of glass/epoxy and jute/epoxy composites using analytical, numerical, and experimental methods.…”
Section: Sandwich Structures Made Of Non-wood Cellulose Natural Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…They investigated the effects of some parameters such as filler content, jute fibers orientation, and core thickness on the bending, ballistic, and compression characteristics of the developed structure. Using waste materials and natural-based fibers, Balcioglu [142,143] analyzed the flexural, tensile, and compressive properties of sandwich structures consisting of vehicle tire rubber in the core and woven jute/epoxy composite in the face sheets. Rajole et al [144,145] analyzed the impact response of jute/epoxy/rubber sandwich panels and compared their performance with that of glass/epoxy and jute/epoxy composites using analytical, numerical, and experimental methods.…”
Section: Sandwich Structures Made Of Non-wood Cellulose Natural Fibersmentioning
confidence: 99%
“…In addition to using natural fibers, one of the ways to reduce environmental pollution is to use waste materials in engineering structures. Sandwich structures are among those components in which waste materials such as used vehicle tires [142,143], bottle caps [212,267], waste cords [268], headlamp and seat waste [269], packaging wastes [270] can be used well, especially as their core which does not require significant stiffness (see Figure 23). Therefore, it is suggested to focus on manufacturing and analyzing the behavior of sandwich panels with natural fibers in the face sheets and waste materials in the core.
Figure 23.(a) Manufacturing mold, (b) caps attached to first face sheet, and (c) manufactured T-peel sample [267].
…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Piti 42 explored the use of crumb rubber in precast concrete panel and reported that replacing fine aggregate with crumb rubber improved thermal and sound properties. Balcioglu 43 manufactured composite sandwich panels using waste tires as the core material and jute fiber woven‐fabric as wythes. The panels were tested on small scale under three‐point loading and shear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Balcıoğlu, çalışmasında atık taşıt lastiklerini geri dönüşüm sonrası için çekirdek malzemesi olarak kullanıp jüt kumaş ile sandviç kompozit üretmiş ve eğilme davranışını incelemiştir. Yeni kompozitin eğilme davranışının, geri dönüşüm sonrası lastik tanecik boyutuna göre değiştiğini saptamıştır [2]. Büyükkaya, yürüttüğü çalışmada atık fındık kabuklarını geri dönüşüm sonrasında polimetilmetakrilat (PMMA) matris ile üretip yeni kompozit malzemenin kırılma ve eğilme davranışlarını incelemiştir [3].…”
Section: Introductionunclassified